2022
DOI: 10.1021/acs.jmedchem.2c01551
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Macrocycle-Based HPK1 Inhibitors for T-Cell-Based Immunotherapy

Abstract: Hematopoietic progenitor kinase 1 (HPK1) is a negative regulator of T-cell activation, and targeting HPK1 is considered a promising strategy for improving responses to antitumor immune therapies. The biggest challenge of HPK1 inhibitor design is to achieve a higher selectivity to GLK, an HPK1 homology protein as a positive regulator of T-cell activation. Herein, we report the design of a series of macrocycle-based HPK1 inhibitors via a conformational constraint strategy. The identified candidate compound 5i ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 42 publications
(123 reference statements)
0
7
0
Order By: Relevance
“…Cyclization is an effective strategy to develop novel lead compounds by increasing structural novelty, expanding scaffold diversity and taming complexity. Lin et al at Prelude Therapeutics initiated a project to discover potent and selective PRMT5 inhibitors employing this cyclization strategy. The conformation of compound 1 was initially restricted via a five-membered ether in their new inhibitor design, as exemplified by compound 2 (Figure ).…”
Section: Prmt5 Inhibitorsmentioning
confidence: 99%
“…Cyclization is an effective strategy to develop novel lead compounds by increasing structural novelty, expanding scaffold diversity and taming complexity. Lin et al at Prelude Therapeutics initiated a project to discover potent and selective PRMT5 inhibitors employing this cyclization strategy. The conformation of compound 1 was initially restricted via a five-membered ether in their new inhibitor design, as exemplified by compound 2 (Figure ).…”
Section: Prmt5 Inhibitorsmentioning
confidence: 99%
“…6 ). 94 PB2 is a subunit of influenza RNA-dependent RNA polymerase and it is an important target for the design of anti-influenza drugs. The structure of these new 2(1 H )-pyrazinones was based on VX787 ( 66 ), a PB2 inhibitor that has entered phase III clinical trials, by replacing the pyrimidine ring with a pyrazinone moiety.…”
Section: Synthetic Approachesmentioning
confidence: 99%
“…This compound was confirmed to suppress tumor growth by promoting anticancer immune responses in the 4T1 syngeneic mouse model . Compounds 2 – 6 were reported as selective HPK1 inhibitors with single-digit nanomolar or picomolar HPK1 inhibitory activity. , However, these compounds generally displayed moderate inhibition on the cellular phosphorylation of SLP76, a substrate of HPK1, and only compounds 2 and 6 were verified in vivo in the mouse model. In the MC38 syngeneic tumor model, compound 2 in combination with an anti-PD1 antibody displayed synergistic antitumor efficacy.…”
Section: Introductionmentioning
confidence: 98%
“…However, this compound suffered from poor metabolic stability both in mouse and human liver microsomes . Similarly, the macrocyclic compound 6 showed remarkable high potency against HPK1 with an IC 50 value of 0.8 nM, but modest potency was observed in the inhibition of the formation of pSLP76 (IC 50 , 0.6 μM) . All of these results indicated that most of the currently reported HPK1 inhibitors are not optimal for the clinical study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation